2009
DOI: 10.1161/circulationaha.108.799015
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Air Pollution Exaggerates Adipose Inflammation and Insulin Resistance in a Mouse Model of Diet-Induced Obesity

Abstract: Background There is a strong link between urbanization and type 2 diabetes mellitus. Although a multitude of mechanisms have been proposed, there are no studies evaluating the impact of ambient air pollutants and the propensity to develop type 2 diabetes mellitus. We hypothesized that exposure to ambient fine particulate matter (<2.5 μm; PM2.5) exaggerates diet-induced insulin resistance, adipose inflammation, and visceral adiposity. Methods and Results Male C57BL/6 mice were fed high-fat chow for 10 weeks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
493
6
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 659 publications
(548 citation statements)
references
References 45 publications
30
493
6
8
Order By: Relevance
“…Insulin resistance is a main potential mechanism explaining the associations mentioned earlier. Both experimental and epidemiologic studies suggest that environmental exposures to air pollutants can increase the risk of insulin resistance, which may lead to an obvious link between air pollution and type 2 diabetes mellitus (35,36,37). Inflammation is another potential mechanism explaining the associations reported in this meta-analysis.…”
Section: European Journal Of Endocrinologymentioning
confidence: 72%
See 1 more Smart Citation
“…Insulin resistance is a main potential mechanism explaining the associations mentioned earlier. Both experimental and epidemiologic studies suggest that environmental exposures to air pollutants can increase the risk of insulin resistance, which may lead to an obvious link between air pollution and type 2 diabetes mellitus (35,36,37). Inflammation is another potential mechanism explaining the associations reported in this meta-analysis.…”
Section: European Journal Of Endocrinologymentioning
confidence: 72%
“…Previous studies also suggest that PM2.5 can recruit inflammatory cells via CC chemokine receptor 2-dependent mechanism, which is a known inflammatory mechanism in the pathogenesis underlying the association between air pollution and type 2 diabetes (35,41). In addition, previous experimental studies also show that tumor necrosis factor-a, interleukin-6, and leptin levels are also elevated on exposure to PM2.5, which suggests that exposure to ambient PM2.5 can be associated with elevated proinflammatory biomarkers and inflammatory responses (37,39,40). It is clear that further data from both experimental and epidemiologic studies are needed to provide more insights into the adverse effect of air pollution on type 2 diabetes risk.…”
Section: European Journal Of Endocrinologymentioning
confidence: 94%
“…For instance, long-term PM 2.5 exposure resulted in systemic inflammation, increased visceral adiposity, and insulin resistance among mice on a high fat diet. 52 In mice consuming normal diets, PM exposure was a risk factor for the development of type II diabetes, as it induced insulin resistance and impaired glucose tolerance. 53 Similarly, in humans, long-term exposure to particulate matter was linked to increased risk of type II diabetes in a large cohort study.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the research conducted for chemical responses employs animal studies, where outcomes and trans-generational responses can be observed in a relatively short period of time. 127,147,148,[174][175][176] Based on the selection scheme detailed in this paper's methodology, only 33% of the studies included in the literature review considered environmental chemical exposures that were not a consequence of prenatal cigarette smoke exposure or physicianprescribed medications. The most common chemical exposures included perfluorinated compounds, phthalates, and outdoor air pollution.…”
Section: Discussionmentioning
confidence: 99%